KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN SIGI DALAM MENJALANKAN TUGAS DAN FUNGSI - Ferra, Ferra (Katalogis, 2015)
This research aims at finding out whether the performance of the Parliament Secretariat employees at Sigi Regency in carrying out their duties and functions has been categorized well. This is a qualitative research in term of case study. The setting and the informants were chosen purposively. The data were analyzed gradually based on the information which were obtained from observations, interviews, and documentations. This research employs five indicators of Agus Dwiyanto’s theory to measure the employees’ performance in public service, namely productivity, service quality, responsiveness, responsibility, and accountability. Of those five performance indicators, productivity, service quality, and accountability are not running as expected and still categorized as unsatisfying. While responsiveness and responsibility indicators are tolerably good because the responsiveness indicator has given a description of the ability in recognizing the public desire and the priority programs organizing which would be accomplished. The responsibility is also categorized as good because the programs have run based on administration principles and based on the real principles. Therefore, the parliament secretariat employees can perform their duties and functions effectively and efficiently in improving public service.